O‘ZBEK BOLALAR NUTQINING KORPUS ASOSIDA PSIXOLINGVISTIK TADQIQI («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article covers the study of Uzbek children’s speech and its scientific and practical significance. The article analyzes the study of children’s speech based on the corpus, psycholinguistic analysis, and the anthropocentric study of Uzbek children’s speech.
Keywords: corpus linguistics, experiment, psycholinguistics, speech ontogeny.